Kinetic studies of mercury adsorption in activated carbon modified by iodine steam vapor deposition method. (15th January 2017) - Zhong, Longchun; Li, Wenhan; Zhang, Yongsheng; Norris, Pauline; Cao, Yan; Pan, Wei-Ping
Highlights: The iodine vapor deposition method was put forward to modify the raw activated carbon. AC modified by the iodine steam vapor deposition method has good mercury adsorption capacity. The pseudo-second model was the best fit to the actual mercury adsorption behavior onto AC-I2 sorbent. A general dynamic equation was determined to predict mercury adsorption by AC-I2 sorbent. Abstract: The objective of this study was to develop a high efficiency activated carbon (AC) sorbent for mercury removal. The vapor deposition method was used to modify the raw AC. This method is relatively easy to carry out and uniformly modifies the AC. The results of this study indicate that AC modified by iodine steam vapor deposition has much better Hg capturing capacity than AC modified by bromide deposition under the same experimental conditions. London dispersion forces and exposure of the sorbent surfaces play important roles in elemental mercury (Hg 0 ) adsorption. Adsorption kinetic behavior was also studied under different experiment conditions. Results indicated that the pseudo-second model was the best fit to the actual mercury adsorption behavior onto AC-I2 sorbent. The effect of adsorbent mass and gas flow rate on adsorption behavior were examined. Results indicated that increasing the sorbent mass led to an increase in Hg adsorption capacity, while increasing the gas flow rate resulted in a significant decrease in Hg adsorption capacity. Decreases in Hg adsorption capacity were likely due to a shorter contact time and lower partial pressure reducing the number of contact opportunities between the Hg atoms and the sorbent surface. Finally, a general dynamic equation was determined that can be used to help predict Hg adsorption curve of AC-I2 sorbent without completing a real fixed-bed Hg adsorption experiment.